Pengaruh Strategi Usaha, Inovasi, Dan Fokus Pelanggan Terhadap Kinerja Organisasi Melalui Keunggulan Kompetitif - Apridyta Rachma Aryani; Indarto Indarto; Yuli Budiati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study is based on quantitative research based on the fact that the company's sales have been unstable for several years due to national phenomena. The purpose of research on the problem is to analyze the impact of business strategy on organizational performance. This study used questionnaires or interviews with respondents, measuring variables using intervals. The technique used is descriptive analysis. The results showed that the business strategy variable did not have a significant effect on organizational performance. And competitive advantage cannot affect the company's performance and business strategy. In short, business strategy variables do not affect competitive advantage. In other words, the higher the existing strategic effort, the smaller the influence of new competitive advantage. Using resource-based theory as the main theory, resource-based theory is a theory which states that companies can: Increase competitive advantage. you by developing resources that help you survive in the long term. Keywords: Competitive Advantage; Organizational performance; Business strategy